Perceptions of Decision-making in Accessing Reproductive Healthcare Services of Urban Women - Rahman, Md Mahbubur; Tabassum, Taniza; Rahman, Md Shafiqur; Uddin, Abu Noman Mohammed Mosleh; Ahmad, Mushtaq; Ferdousi, Shammi Sultana; Wahab, Md Abdul (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Women’s healthcare during the reproductive period of life, especially decisions involving her own health is generally one of the least concerns to the common people. Women’s autonomy in decision-making within the family is fairly debatable and determines the health service seeking behaviour. Objective: To find out the perceptions about key persons involved in decision-making for accessing reproductive healthcare services as well as factors that influence those decisions among urban women of Bangladesh. Materials and Methods: The study was conducted by key informant interviewing (KII) of 72 respondents about their perceptions of decision-making in women’s reproductive health services in Dhaka South City Corporation during the period of January 2019 to April 2019. Health professionals of various levels, administrators, family heads were selected as key informants by purposive sampling method. An open-ended semi-structured questionnaire was used for data collection. Result: Among the key informants, more than half were doctors (58.3%). The majority of the respondents were female (72%) and having educational qualification up to graduate level (40.3%). Majority of the informants (73.9%) mentioned ‘both parents’ as key persons in under 18 marriage of their daughters; 57.1% of respondents opined that ‘Factors like social environment, social status, uncertainty to find better groom, dowry etc.’ influences in decision-making. All of the respondents felt antenatal care ‘essential’ and about half of them (50.0%) mentioned the importance of complication detection and treatment during pregnancy. According to the respondents, ‘mother-in-law’ is the key person in women’s decision-making regarding antenatal care (65.3%) and ‘husband’ is the key person regarding selection of the place of delivery and postnatal care (79.2%, 72.2%) respectively. Half of the respondents (50%) expressed the family size determination in an urban area is done mutually by ‘both partners’ while the role of the ‘husband’ is still perceived important (41.7%). Majority expressed that economic condition of the family (63.9%) have an influence in determining family size by the respondents. According to more than half of the respondents (52.8%), both partners take part in decision-making regarding family planning. Conclusion: Although the educated employed women enjoy some degree of autonomy in urban areas of Bangladesh, the decision-making in accessing woman’s reproductive healthcare services is directed by the husband. Involvement of both partners in decision-making is essential for better utilization of reproductive health services. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 15-20